Regional Planning Cartography - Sukoco, M (Forum Geografi, 1990)
On the development of regions, whatever they are cannot be separated from the planning stage beforeÂ the development stage it self. This paper aims to investigate the role of artography, in relationÂ with the study of regional development, especially in relation with the preparation of map types that are relevant and need for both planning and regional development processes. Planners have agreed that maps are highly neede in the planning process, but much is still debated as to ways of presentation, contents of theme, and suitable scala for planning purposed. There are two groups of maps neede by planners, i.e. status maps that are neede before planning and maps that are neede during the planning process. The selection of how much information needed to be drawn on maps for the aims of regional planning, is a difficult problem to solve and also challenge for us, especially geographers. This paper is only a desription of our contribution of thoughts, not based on any research, but is a compilation from various source/ideas, particularly from cartographer who are experienced in their new field, i.e. âRegional Planning Cartographyâ.